Automated Water Condition Monitoring for Grass-Swale Drainage System - Supande, Nor Afiq; Sudin, Nor’aisah; Mohamad Md Som (Evolution in Electrical and Electronic Engineering, 2020)
In the ‘Internet of Things’ (IoT) based drainage monitoring, data collection, and information analysis through various sensors will play an important role in the future, and it will be a core technology to develop IoT-based drainage monitoring systems. This project focused on the Monitoring Grass Swale-Drainage System using Arduino based on the IoT module in the Irrigation and Drainage industry. One of the conventional methods used by researchers is to instruct technical staff to visit the drainage at the appointed time and perform manual tests in the laboratory to analyze the quality of the irrigation system. Because of this, it requires a lot of time and effort. Therefore, this project emphasizes the wireless IoT module system to collect information from various sensors to monitor the drainage via the internet. The project was developed using an Arduino microcontroller, ‘Wi-fi Ethernet Shield’, multiple sensors such as ultrasonic, rain detector, and flowrate sensor. Parameter value readings which are water level and total flow discharge velocity will be sent from the Arduino subsystem to the ‘Wi-fi Ethernet Shield’ module and then displayed on the Android smartphone apps. Next, the information sent to the IoT platform ThingSpeak can also be reviewed by researchers such as hydraulic parameters or weather conditions. The project proposes a monitoring system that emphasizes aspects such as low cost, fast and real-time data acquisition, easy installation, and easy operation.